Design and performance analysis of a regenerative evaporative cooler for cooling of buildings in arid climates - Boukhanouf, Rabah; Amer, Omar; Ibrahim, Hatem G.; Calautit, John Kaiser (Elsevier, 2018)
Evaporative cooling has been considered a low energy consumption process that often is associated with displacement ventilation and passive cooling strategies of buildings. While significant energy savings can be accrued from using evaporative cooling, there are many design challenges to improve the processes of heat and mass transfer and reduce design complexities. This paper seeks to advance the design of evaporative cooling through building and testing a novel regenerative evaporative cooler prototype. It proposes a design that integrates heat pipe and porous ceramic tube modules as an alternative to plate heat exchangers. The paper describes design arrangement of the cooler, a mathematical model and laboratory test results. Under controlled laboratory test conditions, the measured performance indices of wet bulb effectiveness, specific cooling capacity and coefficient of performance (COP) were determined as 0.8, 140 W per m2 of wet ceramic surface area and 11.43 respectively. Furthermore, experimental results show that under typical ambient conditions commensurate with that prevailing in arid climates, the cooler air supply temperature was as much as 14 oC below that of the ambient air.